Policy Factors in Ethnic Conflicts in Myanmar—An Example of Ethnic Issues in Rakhine State - Yang, Dawei (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
Ethnic conflicts have long constrained Myanmar’s domestic political, economic and social development, and the ethnic issues in Rakhine State are particularly complex. As the main ethnic group in Myanmar, the Burmese maintain their dominant position in the trilateral game of “Burmese-Rakhine-Rohingya” in Rakhine State by means of the central government’s ethnic differentiation policies, religious and cultural policies, and party election policies. However, this has resulted in an increase in ethnic violence, the rise of Buddhist nationalism, and the growth of the Arakan National Party. And national policies play a catalytic or inducing role in the transmission process of social foundations and ethnic conflicts, by changing the environment of interethnic relations to facilitate ethnic mobilization. As the central government’s policies have failed to effectively resolve the differences in interests among local ethnic groups and maintain harmonious ethnic relations, the existing identity differences such as ethnicity, religion, and parties have become tools for a small number of ethnic elites to achieve political goals, exacerbating ethnic conflicts in Rakhine State.